PENGARUH CURRENT RATIO DAN TOTAL ASSET TURNOVER TERHADAP RETURN ON ASSET PADA PT ACE HARDWARE INDONESIA, TBK PERIODE 2013-2022 - Vera Agistiani; Lativa Lativa (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to determine the effect of Current Ratio and Total Asset Turnover on Return On Assets at PT Ace Hardware Indonesia, Tbk for the 2013-2022 period. The method used in this thesis is quantitative descriptive, the population in this research is the financial report of PT Ace Hardware Indonesia, Tbk and the sample used is the financial position report and profit and loss report for 2013-2022. This data was obtained from the official website of the company PT Ace Hardware Indonesia, Tbk. The results of this research showed that the results of hypothesis testing using the t test showed that the Current Ratio (CR) variable had Thitung < Ttable, namely 1.698 < 2.365 and a significance value of 0.133. This means that it can be said that the Current Ratio (CR) does not have a partially significant influence on Return On Assets (ROA) at PT Ace Hardware Indonesia, Tbk for the 2013-2022 period. The results of hypothesis testing using the t test showed that the Total Asset Turnover (TATO) variable had Thitung > Ttable, namely 9.511 > 2.365 and a significance value of 0.000. It can be said that Total Asset Turnover (TATO) has a significant influence on Return On Assets (ROA) at PT Ace Hardware Indonesia, Tbk for the 2013-2022 period. Meanwhile, based on the f test results, the Fhitung > Ftable value was obtained, namely 55.975 > 4.46 and a significance value of 0.000. It can be said that the Current Ratio (CR) and Total Asset Turnover (TATO) together or simultaneously have an influence on Return On Assets (ROA) at PT Ace Hardware Indonesia, Tbk for the 2013-2022 period. The results of the determination test show Adjust R2 = 0.941 or 94.1%. This value shows that the ability to explain ROA through CR and TATO is 94.1% and the remaining 5.9% is explained by other variables.